Ankle inversion proprioception measured during landing in individuals with and without chronic ankle instability. Issue 7 (July 2021) - Han, Jia; Yang, Zonghan; Adams, Roger; Ganderton, Charlotte; Witchalls, Jeremy; Waddington, Gordon
Abstract: Background: Research evidence has suggested that a more sensitive ankle proprioceptive testing method with higher ecological validity is needed for assessing proprioceptive deficits in individuals with chronic ankle instability (CAI). Objectives: (1) To determine the test–retest reliability of a novel ankle proprioception assessment tool, the Ankle Inversion Discrimination Apparatus for Landing (AIDAL); (2) To assess whether AIDAL scores were sufficiently sensitive to detect proprioceptive deficits in chronic ankle instability (CAI); and (3) To examine whether AIDAL scores correlated with Cumberland Ankle Instability Tool (CAIT) scores. Design: Cross-sectional study. Methods: The AIDAL was purpose-built to assess ankle discrimination in four positions of ankle inversion (10°, 12°, 14° and 16°) upon landing from a 10 cm drop. Area Under the Receiver Operating Curve (AUC) was employed as the ankle proprioceptive discrimination score. Seven-day test–retest reliability was evaluated with 23 university students (12 CAI and 11 non-CAI), and another 36 university students (18 CAI and 18 non-CAI) were in the comparison study. Results: The test–retest reliability ICC score for the whole group was 0.763 (95% CI = 0.519–0.892), which showed an excellent reliability level. ICC (3, 1) was 0.701 for the non-CAI group (95%CI = 0.210–0.910) and 0.804 for the CAI group (95%CI = 0.451–0.939). The CAI group performed at a significantly lower level on the AIDAL assessment than the non-CAI group (0.777 ± 0.05 vs. 0.815 ± 0.05, F  = 5.107, p  = 0.03). The discriminative AUC value for the AIDAL test was 0.756 with a cut point of 0.819 (sensitivity = 0.733, specificity = 0.800). The MDC90 scores for CAI and non-CAI groups were both 0.04. Spearman's correlation showed that the CAIT scores were significantly correlated with the ankle proprioceptive discrimination scores ( rho  = 0.401, p  = 0.015). Conclusion: The AIDAL showed good test–retest reliability for both non-CAI and CAI groups. Measuring ankle inversion proprioception during landing may be important for assessing the outcomes of CAI rehabilitation, as proprioceptive performance obtained from the AIDAL was significantly correlated with severity of functional ankle instability CAIT scores.